UMP focuses on improving the quality of higher education - Mimi Rabita, Abdul Wahit (2020)
Universiti Malaysia Pahang (UMP) will continue to strengthen efforts in developing and expanding higher education by focusing on the field of Technical and Vocational Education and Training (TVET).